Money hungry - Flake, Sharon (New York : Jump at the Sun/Hyperion Books For Children, 2001)
All thirteen-year-old Raspberry can think of is making money so that she and her mother never have to worry about living on the streets again.
Sequel: Begging for change.
Keywords: Money -- Fiction; Mothers and daughters -- Fiction; Single-parent families -- Fiction; Inner cities -- Fiction; City and town life -- Fiction; African Americans -- Fiction